Efficient Scheduling of Pigeons for a Constrained Delay Tolerant Application. (13th December 2009) - Zhou Zhou, Jiazhen Jiazhen; Li Li, Jiang Jiang; Burge Burge, Legand Legand
Abstract : Information collection in the disaster area is an important application of pigeon networks—a special type of delay tolerant networks (DTNs) that borrows the ancient idea of using pigeons as the telecommunication method. The aim of this paper is to explore highly efficient scheduling strategies of pigeons for such applications. The upper bound of traffic that can be supported under the deadline constraints for the basic on-demand strategy is given through the analysis. Based on the analysis, a waiting-based packing strategy is introduced. Although the latter strategy could not change the maximum traffic rate that a pigeon can support, it improves the efficiency of a pigeon largely. The analytical results are verified by the simulations.